DINAMIKA REAKTOR VENTURI BERSIRKULASI (RVB) - Hidayati, Nur
Abstract : Loop-Venturi Reactor (LVR) consists of a reaction vessel, venturi or ejector, and liquid circulation. Ejector or venturi is used for sucking and dispersing the gas phase in the liquid as bubbles. LVR are particularly suitable for fast reactions in which gas-liquid mass-transfer is in the reaction limiting step of the process. The benefits of LVR are the ability to offer high mass-transfer coefficient, both for the ejector and total reactor system. Ejector could provide the interfacial area from 40,000 to 70,000 m2/m3, and the total system could reach 500-2,500 m2/m3. Recently, the LVR could be recommended for fast reactions. LVR has been growth up since past three decennia. The most widely known LVR has been commercialized by Buss Ltd. in Switzerland and is known as the Buss Loop Reactor. They have built 33, mainly in Europe. Then, the rapid growth of LVR is followed by researches to understand the hydrodynamics and mixing process in the reactor. Both of them are very important to mass-transfer characteristic. The aim of this paper is to study the dynamics and mixing process of gas-liquid in LVR. These topics include hydrodynamics, mass-transfer characteristic, and some factors that affecting to hydrodynamics and mass-transfer characteristic. Hydrodynamics of LVR studied consists of flow regime, gas hold up, and pressure differential across the ejector. There are four flow regimes in the ejector, i.e. slug, annular, bubble, and jet flow. Pressure differential across the ejector determines energy dissipation rate for form bubbles. Also, energy dissipation rate influences the gas-liquid interfacial area and mass-transfer coefficient. Factors that affecting hydrodynamics and mass-transfer characteristic are physically fluid properties, swirling effect to the liquid jet, and ejector geometric parameters.